2013
DOI: 10.1179/1743280413y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative X-ray tomography

Abstract: X-ray computer tomography (CT) is fast becoming an accepted tool within the materials science community for the acquisition of 3D images. Here the authors review the current state of the art as CT transforms from a qualitative diagnostic tool to a quantitative one. Our review considers first the image acquisition process, including the use of iterative reconstruction strategies suited to specific segmentation tasks and emerging methods that provide more insight (e.g. fast and high resolution imaging, crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
601
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,062 publications
(627 citation statements)
references
References 429 publications
1
601
0
Order By: Relevance
“…93 Focused ion beam-scanning electron microscope (FIB-SEM) slice and view tomography, 94 and X-ray computed tomography (X-ray CT) 95 are among the most prominent methods of reconstructing a sample in three dimensions. Even though the operation and image acquisition of both method is radically different, comparative studies showed, that acquired data is identical when the resolution is the same.…”
Section: Tortuosity Calculation In 3d Volumesmentioning
confidence: 99%
“…93 Focused ion beam-scanning electron microscope (FIB-SEM) slice and view tomography, 94 and X-ray computed tomography (X-ray CT) 95 are among the most prominent methods of reconstructing a sample in three dimensions. Even though the operation and image acquisition of both method is radically different, comparative studies showed, that acquired data is identical when the resolution is the same.…”
Section: Tortuosity Calculation In 3d Volumesmentioning
confidence: 99%
“…cubic cell and Voronoi structure, but they may not be able to sufficiently capture the actual structural effect of foam materials, since some factors such as cell-wall rate dependence and micro inertia depend on the actual structural characteristics [8]. This motivates the geometrically EPJ Web of Conferences realistic simulations based on cell structures obtained from computed tomography (CT) images (so-called imagebased modelling [9]), which has been employed to investigate the strain-rate sensitivity of open-cell foams [10,11] and the quasi-static compressive behaviour of closed-cell foams [12,13]. The dynamic behaviour of Alporas foam has yet to be examined in this way.…”
Section: Introductionmentioning
confidence: 99%
“…There are several tools available for 3D characterization e.g. X-ray computed Tomography (CT) [1], Serial Sectioning SEM Tomography (SST) [2,3], transmission electron microscopy [4] and Atom Probe [5]. Figure 1 demonstrates their complementarity in terms of the lengthscales they can access.…”
mentioning
confidence: 99%
“…However the limited volumes accessible through the Gallium Ion FIB present a severe limitation. The size of the volume that can be examined via SST and the depth from which the regions of interest identified by X-ray CT is also key to opening up possibilities through a correlative tomography framework [1]. There are many scenarios in materials science that require analysis across length-scales up to many 100's of microns that lie beyond what a Ga ion FIB can typically access, relating to grain microtextures, grain neighborhoods, grain boundaries, inclusions and cracks.…”
mentioning
confidence: 99%